RELATIONS OF TOURISM AND HOTEL MANAGEMENT WITH RESPECT TO GDP GROWTH OF REPUBLIC OF SRPSKA - Lazarević, Momir (ECONOMICS - INNOVATIVE AND ECONOMICS RESEARCH JOURNAL, 2017)
Tourism is the fastest growing and one of the most profitable industries in the world, with countless opportunities for the economic development of the regions. One should not view tourism and hospitality as separate concepts, since one can neither exist nor can be sustained without the other. A tourist, besides wanting to see and get to know the attractiveness of a place, wants to be offered a satisfactory level of basic (food, accommodation, transport) and additional (entertainment, recreation, shopping. . ) services which will certainly have an influence on his satisfaction and the desire to return. If we don’t turn to socially responsible behavior, we will lose the conditions for the development of tourism, and therefore a possible basis for social and economic prosperity as a result of such a sustainable tourism. Globalisation also appears as a threat of uniformity of everything that surrounds us, because different societies, economies and cultures are increasingly intertwined and thus endanger the identity of one nation, its customs, folklore and overall cultural creativity.